Avaliação da viabilidade técnico-econômica do processo de hidrogenação seletiva de CO2 a metanol - Silva, Kaio Martins Pedro da (Universidade Federal de São Carlos, 2025)
This work evaluates the techno-economic feasibility of the selective hydrogenation of carbon dioxide (CO₂) to methanol, in response to the growing demand for cleaner energy sources and the global commitment to reducing greenhouse gas emissions. Methanol is a key chemical in both the chemical and energy industries, serving as a feedstock for various products or as an energy carrier. Its production from CO₂ and green hydrogen represents a promising alternative for residual carbon valorization and environmental impact mitigation. The study employs process modeling using Aspen Plus for thermochemical and phase equilibrium simulation, and Aspen Process Economic Analyzer for the economic assessment. The proposed industrial-scale model includes feed compression, catalytic reaction under optimized conditions (200 °C, 50 and 100 bar), and product separation. Operating parameters were selected based on experimental data from the literature to reflect realistic and technically feasible scenarios. A multivariate economic analysis was conducted through a design of experiments matrix that considered variations in feedstock prices (CO₂, H₂, CO) and plant lifetime. Key economic indicators were calculated, including capital expenditures (CAPEX) ranging from USD 9.7 to 12.0 million, operating expenditures (OPEX) from USD 6.2 to 8.5 million/year, minimum selling price (MSP) of methanol between USD 1.85 and 3.84/kg, and net present value (NPV) as low as USD 738 million. The results highlight the main technological bottlenecks and suggest process improvements to enhance viability. Despite current challenges, particularly the high cost of green hydrogen, future scenarios with decarbonization incentives and technological advancements may enable the economic feasibility of this sustainable route.
Evaluation of the technical and economic feasibility of the selective hydrogenation process of CO2 to methanol
Keywords: Hidrogenação de CO₂; Produção de metanol; Análise técnico-econômica; Simulação de processos; Sustentabilidade industrial; CO₂ hydrogenation; Methanol production; Techno-economic analysis; Process simulation; Industrial sustainability; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura; 7. Energia limpa e acessível